2014
DOI: 10.3390/toxins6103028
|View full text |Cite|
|
Sign up to set email alerts
|

Aflatoxin B1 Degradation by a Pseudomonas Strain

Abstract: Aflatoxin B1 (AFB1), one of the most potent naturally occurring mutagens and carcinogens, causes significant threats to the food industry and animal production. In this study, 25 bacteria isolates were collected from grain kernels and soils displaying AFB1 reduction activity. Based on its degradation effectiveness, isolate N17-1 was selected for further characterization and identified as Pseudomonas aeruginosa. P. aeruginosa N17-1 could degrade AFB1, AFB2 and AFM1 by 82.8%, 46.8% and 31.9% after incubation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
68
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 35 publications
15
68
1
Order By: Relevance
“…A number of studies have evaluated intrinsic factors, including carbon source [26,34], nitrogen source [26,34,88], vitamins [26], metals ions [12,34,46,89,90,91,92,93], enzyme inhibitors and promoters [52,89,90,91,92,93,94], initial concentration of mycotoxins [93,95], initial concentration of cells [53,95] and initial pH value [12,14,17,26,31,34,41,46,54,60,88,89,95,96], as well as extrinsic factors, including temperature [12,14,17,25,26,31,34,38,41,46,52,54,60,88,89,95,96], aeriation (shaking rate) [26], oxygen preference [14], as well as pre-incubation [26] and incubation time [34,97]. The experimental designs and optimized biotransformation conditions are summarized in Table 2.…”
Section: Strategies and Methodologiesmentioning
confidence: 99%
“…A number of studies have evaluated intrinsic factors, including carbon source [26,34], nitrogen source [26,34,88], vitamins [26], metals ions [12,34,46,89,90,91,92,93], enzyme inhibitors and promoters [52,89,90,91,92,93,94], initial concentration of mycotoxins [93,95], initial concentration of cells [53,95] and initial pH value [12,14,17,26,31,34,41,46,54,60,88,89,95,96], as well as extrinsic factors, including temperature [12,14,17,25,26,31,34,38,41,46,52,54,60,88,89,95,96], aeriation (shaking rate) [26], oxygen preference [14], as well as pre-incubation [26] and incubation time [34,97]. The experimental designs and optimized biotransformation conditions are summarized in Table 2.…”
Section: Strategies and Methodologiesmentioning
confidence: 99%
“…(Guan et al, 2008), Nocardia corynebacteroides (Tejada et al, 2008), Rhodococcus erythropolis (Alberts et al, 2006;Cserhati et al, 2013;Teniola et al, 2005), Myxococcus fulvus (Zhao et al, 2011) and Pseudomonas spp. (Krifaton et al, 2011;Samuel et al, 2014;Sangare et al, 2014). Likewise, a number of fungal strains such as Armillariella tabescens (Liu et al, 2001), Phanerochaete sordida (Wang et al, 2011), Pleurotus ostreatus (Yehia, 2014) and a host of others (Adebo et al, 2015;Alberts et al, 2009;Wu et al, 2009) have been found to transform AFB 1 to less toxic products.…”
Section: Introductionmentioning
confidence: 99%
“…The same is observed with Pseudomonas species and yeasts: they have been mentioned to degrade mycotoxins, but they are also rather undesirable in silages . Pseudomonas species have been identified to degrade aflatoxins and zearalenone . The yeast S. cerevisiae has been reported to degrade trichothecenes, enniatins, ochratoxin A, patulin and beauvericin .…”
Section: Remediation Of Mycotoxins In Silagesmentioning
confidence: 99%